1979
DOI: 10.1111/j.1365-2923.1979.tb00928.x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of three types of multiple choice questions

Abstract: The present study reports the results of an evaluation of three types of multiple choice questions--the five choice completion, and assertion-reason. Fifty-four questions, eighteen of each type and measuring the candidate on the same scientific principle and classified as either factual or comprehension, were developed and included in the General Surgery certifying examination of the Royal College of Physicians and Surgeons of Canada. In addition to using descriptive statistics, the multitrait-multimethod tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Although Skakun et al (1979) reported that A‐, K, and E‐ (assertion‐reason) type items were unable to discriminate among cognitive traits, our department has, over the years, used three different item‐types in anatomy MCQ tests. According to Lipton & Huxham (1974), an important need met by such a practice is defined by the fact that the presentation of certain problems is often better suited to a given item‐type than to others.…”
Section: Discussionmentioning
confidence: 99%
“…Although Skakun et al (1979) reported that A‐, K, and E‐ (assertion‐reason) type items were unable to discriminate among cognitive traits, our department has, over the years, used three different item‐types in anatomy MCQ tests. According to Lipton & Huxham (1974), an important need met by such a practice is defined by the fact that the presentation of certain problems is often better suited to a given item‐type than to others.…”
Section: Discussionmentioning
confidence: 99%
“…It is quite surprising, therefore, that the academic literature on the subject is quite sparse. Connelly (2004) provides an overview of the existing published material (see Newble et al, 1979;Skakun et al, 1979;Fox, 1983;and Scouller & Prosser, 1994) before going on to extol the main virtue of the ARQ test item; viz. that 'its structure facilitates the construction of questions that test student learning beyond recall.…”
Section: Assertion-reason Multiple-choice Testing 291mentioning
confidence: 99%
“…2,3 In recent years, the most common type of MCQs employed in examinations are type A MCQs, which consist of a stem followed by four or five options or distractors. 4,5 An item analysis assesses the reliability and validity of an examination by examining student performance with regards to each MCQ and applying statistical analyses to determine whether the item should be kept, reviewed or discarded from the test. Common item analysis parameters include the difficulty index (DIFI), which reflects the percentage of correct answers to total responses; the discrimination index (DI), also known as the point biserial correlation, which identifies discrimination between students with different levels of achievement; and distractor efficiency (DE), which indicates whether the distractors in the item are well-chosen or have failed to distract students from selecting the correct answer.…”
mentioning
confidence: 99%